Impact of macrophage infiltration in patients with st-segment elevation myocardial infarction caused by plaque erosion: an in vivo optical coherence tomography study. (25th November 2020) - Zhao, C; Hu, S; Meng, W; Wang, S; Chen, X; Zeng, M; He, L; Zhao, L; Yu, H; Ren, X; Zhang, S; Hou, J; et al.
Abstract: Background: Chronic inflammatory infiltration is a common process for atherosclerosis development. However, autopsy studies reveal that incidence rate of inflammatory infiltrates are less abundant in plaque erosion compared with plaque rupture. Purpose: Studies performed by optical coherence tomography (OCT) have allowed to establish the severity of plaque inflammation by assessing macrophage infiltration (MØI). In this study, we aimed at assessing the impaction of MØI in plaque erosion among patients with STEMI by using OCT. Methods: A total of 1561 patients with ST-segment elevation myocardial infarctions (STEMI) who underwent OCT imaging were enrolled in this study. According to the exclusion criteria, 312 patients with STEMI exhibiting plaque erosion were classified as MØI or no MØI. Results: 163 (52.2%) patients had MØI at the site of plaque erosion, whereas 149 (47.8%) patients had no evidence of MØI and patients of MØI group were significantly older (P=0.015). The result of angiography showed the prevalence of multi-vessel disease appeared more frequency (P=0.021) and diameter stenosis% were higher (P=0.031) in MØI group. OCT results showed the minimum fibrous-cap thickness was thinner (P<0.001) and the maximum lipid arc was larger (P=0.005) in MØI group. Some patients underwent imaging follow-up at 1 year. There was no significant difference in the culprit plaque morphology progress among two groups (Figure 1A-1D). Conclusions: This study demonstrated that plaque inflammation can increase culprit lesion severity and plaque vulnerability in patients with STEMI caused by plaque erosion. Funding Acknowledgement: Type of funding source: None